Responses of a Newly Evolved Auxotroph of Chlamydomonas to B12 Deprivation. Issue 1 (20th February 2020) - Bunbury, Freddy; Helliwell, Katherine E.; Mehrshahi, Payam; Davey, Matthew P.; Salmon, Deborah L.; Holzer, Andre; Smirnoff, Nicholas; Smith, Alison G.
Abstract : An artificially evolved strain of the model alga Chlamydomonas provides insight into how algal B12 auxotrophy has arisen naturally but also reveals the challenges to becoming B12 dependent. Abstract: The corrinoid B12 is synthesized only by prokaryotes yet is widely required by eukaryotes as an enzyme cofactor. Microalgae have evolved B12 dependence on multiple occasions, and we previously demonstrated that experimental evolution of the non–B12 -requiring alga Chlamydomonas reinhardtii in media supplemented with B12 generated a B12 -dependent mutant (hereafter metE7). This clone provides a unique opportunity to study the physiology of a nascent B12 auxotroph. Our analyses demonstrate that B12 deprivation of metE7 disrupts C1 metabolism, causes an accumulation of starch and triacylglycerides, and leads to a decrease in photosynthetic pigments, proteins, and free amino acids. B12 deprivation also caused a substantial increase in reactive oxygen species, which preceded rapid cell death. Survival could be improved without compromising growth by simultaneously depriving the cells of nitrogen, suggesting a type of cross protection. Significantly, we found further improvements in survival under B12 limitation and an increase in B12 use efficiency after metE7 underwent a further period of experimental evolution, this time in coculture with a B12 -producing bacterium. Therefore, although an early B12 -dependent alga would likely be poorly adapted to coping with B12 deprivation, association with B12 -producers can ensure long-term survival whilst also providing a suitable environment for evolving mechanisms to tolerate B12 limitation better.